Professional Bureaucracy and Health Care Managers’ Planned Change Strategies: Governance in Swedish Health Care - Andreasson, Jörgen; Ljungar, Erik; Ahlstrom, Linda; Hermansson, Jonas; Dellve, Lotta (Nordic Journal of Working Life Studies, 2018)
To increase efficiency and quality, process development has been implemented in many Swedish hospitals. These hospitals are usually organized as professional bureaucracies in which health care managers have limited decision control. The new governance principles has been implemented without removing bureaucratic elements. This study analyzes how managers implement planned change in these professional bureaucracies, considering if managers coaching style, organizational preconditions, implementation strategy, appraisal of change and clinic autonomy, is associated with health care process quality (HPQ). The study is based on interviews with health care managers and longitudinal assessments of HPQ. The results revealed significant differences between coaching style, organizational preconditions, and HPQ over time. The conclusion is that leadership and preconditions is of importance for the health care manager’s ability to work with planned change, as that the health care managers understand how management methods, governance principles, and professional bureaucracies work in practice.